In vitro metabolism of different cellulosic feeds by Ruminococcus albus pure culture - KUMAR, SHIV; SANGWAN, D C; SINGH, SADHANA; BHATIA, S K; DULAR, R K (The Indian Journal of Animal Sciences, 2014)
Rumen metabolic activity in vitro by Ruminococcus-albus (cellulolytic bacteria isolated from buffalo) on nutritively variable cellulosic substrates (CP 2.1 to 20.3%, NDF 50.3 to 77.7%, cellulose 26.5 to 39.7%) was profiled. Standard batch culturing technique for different time course (12, 24, 48, 72 and 96 hr) fermentation of 9 substrates like wheat straw, paddy straw. pearlmillet stover, sorghum stover and berseem hay (group 1) and chkkpca straw, sugarcane bagasse, oat hay and alfalta hay (group 2) was followed. Concentration of ruminal nitrogen fractions (barring protein-N which continually elevated up to 96 hr) increased (P<0.05) irrespective of cellulosic feedstuffs, up to 48 hr of incubation. and thereafter declined (P<0.05). However. TVFA contents and cellulase activity, which differed (P<0.05) among substrates, enhanced concomitantly with prolonging the fermentation from 12 hr to 96 hr. The pattern of ruminal metabolites irrespective of experiments remained alike, thereby ostensibly reflected consistency in catabolic and anabolic potential of R. albus pure culture. Straws and stovers which yielded relatively less (P<0.05) NH] -N (average ranged from 24.2 mg in wheat straw to 33.4 mg% in pearlmillet stover) than alfalfa hay (37.3mg%). also exhibited lower (P<0.05) rumen protein-N contents varying from 13.6 to 16.7%. of all the hays, oat hay (18.8mg) maximized (P<0.05) Sorghum stover degradation ironically helped generate more (P<0.05) protein-N (17.9mg%) and TVFA (100.2 meq/L) than the latler 2 hays but values were in proximity of those due to oal hay (18.8 mg, 102.4 meq/L) The protein-N (as per cent of total N) contents were 12.5 (oat hay), 12.2 (sorghum stover), 11.3 (alfalfa hay) and to.9 (berseem hay). Study inferred differential bacterial growth dependent proteoanabolic and cellulolytic activities of R. albus pure culture on varied cellulosics. Sorghum stover exceeded legume hays to anabolise rumen ammonia for pibteosynthesis.